(untitled) (Bangladesh Journal of Agricultural Research, 2016)
The study was conducted in Bogra and Satkhira districts to assess the socioeconomic status, profitability, problems and prospects of sunflower cultivation in Bangladesh. A total of 100 sunflower cultivating farmers, taking 50 farmers from each district, were randomly selected for this study. About 18% female farmers were also found to cultivate sunflower due to its beauty and easy cultivation method. Majority of the farmers had only one year experience of sunflower cultivation. Per hectare cost of producing sunflower was estimated as Tk. 62,199. Per hectare net return and BCR were Tk. 10,863 and 1.18, respectively which indicated that sunflower cultivation was profitable. Stochastic frontier function revealed that the use of labour, seed, organic fertilizers, cost of irrigation, and land type had positive and significant effect on the yield of sunflower. Average technical efficiency of the farmers was 86% which implies that there is a scope of increasing productivity of sunflower by 14% using current level of inputs by increasing the farmers efficiency. Lack of irrigation facility, scarcity of seed on time, absence of sunflower oil mill and sunflower market, low demand for sunflower, high cost of seed, etc. were the major problems of sunflower production and marketing. In spite of having some problems 18% female farmers became interested to cultivate and 46% farmers of Satkhira district mentioned that their demand for edible oil is becoming fulfil. So there is great potentiality of sunflower cultivation in Bangladesh. The availability of sunflower seed with low cost and establishment of sunflower oil mill is needed to sustain this crop in Bangladesh. Therefore, import dependency on soybean oil will be reduced. Bangladesh J. Agril. Res. 41(4): 599-623, December 2016